The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14138080
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Future BEVs Adoption in Croatia

Abstract: Electric vehicles (EVs) represent a revolution and the beginning of a new era in the development of the automotive industry. This study investigates the advantages and disadvantages of battery electric vehicles (BEVs) and the possibilities of their better future adoption in the Republic of Croatia. Based on an in-depth analysis of the current status of BEVs in Croatia, the study shows that the number of passenger BEVs and charging stations are constantly increasing. However, despite the many advantages of BEVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…Consumer attitudes, perceptions, and political actions directly impact the acceptance of new and/or evolving technology. In order to understand the hurdles to entrance and consumer mass adoption of electric vehicles, numerous studies have been done and examined the effects of political and economic support decisions (Emanovic et al, 2022;Ling et al, 2021). The European market contributed 26.29% of global sales for battery electric vehicles and 32.62% for plug-in hybrid vehicles.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Consumer attitudes, perceptions, and political actions directly impact the acceptance of new and/or evolving technology. In order to understand the hurdles to entrance and consumer mass adoption of electric vehicles, numerous studies have been done and examined the effects of political and economic support decisions (Emanovic et al, 2022;Ling et al, 2021). The European market contributed 26.29% of global sales for battery electric vehicles and 32.62% for plug-in hybrid vehicles.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Accordingly, it is a complex, multidimensional concept that needs a set of sustainability indicators rather than a single hand to measure it [10]. As a sequence, the primary concerns of the idea of sustainability are the preservation of the natural environment [11,12], the thermal effect of ecological network factors [13], tourism flow [14], accessibility and economic linkage [15][16][17], hotspots during the COVID-19 pandemic [18], Urban Intelligence for Carbon Neutral Cities [19], the complex structural to deal with the disturbance of emergencies [20], and the walkability [21][22][23][24][25][26][27][28][29]. And to create vibrant and livable cities that support walkability and sustainability, an effort to promote active street network connections must be made with shorter block lengths and many intersections to facilitate more direct travel between locations [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the second challenge, necessity for better information sharing and education was recognized by authors in [11] who analyzed the challenges for adopting EVs in Croatia. However, a big part of the issue has already been solved.…”
mentioning
confidence: 99%
“…A study on a road and a power system segment in Croatia presented in [13] showed that coordination between the transport system planners and power system planners is central to high adoption of electromobility. The authors in [11] emphasize the problem of uneven distribution of charging stations for both domestic adoption of EVs and the highway congestion management during the tourist season.…”
mentioning
confidence: 99%